2004
DOI: 10.1159/000079575
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between male infertility and increased levels of sperm disomy

Abstract: Sperm chromosome abnormalities cut across a number of areas relevant to ICC XV. The association between increased levels of sperm aneuploidy (usually disomy) and male infertility has implications for the sessions on reproduction, sex chromosomes, aneuploidy and meiosis and was, to the best of our knowledge, first reported in 1995. Since then most studies have reported similar increases of varying degrees but, despite this, a small number of laboratories have presented results that demonstrate no significant as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 50 publications
1
44
1
1
Order By: Relevance
“…18 In addition, an increased rate of disomy 21 has been found in infertile patients. 19 We did not observe any significant increase in diploidy, nor in disomy XX, disomy YY or disomy 21. It seems that meiosis I nondisjunction, in this case, is limited to the XY chromosome pair, probably because this bivalent is the most prone to nondisjunction in male gametogenesis.…”
Section: Concurrence Of Alport and Klinefelter Syndromes E Ars Et Alcontrasting
confidence: 50%
See 1 more Smart Citation
“…18 In addition, an increased rate of disomy 21 has been found in infertile patients. 19 We did not observe any significant increase in diploidy, nor in disomy XX, disomy YY or disomy 21. It seems that meiosis I nondisjunction, in this case, is limited to the XY chromosome pair, probably because this bivalent is the most prone to nondisjunction in male gametogenesis.…”
Section: Concurrence Of Alport and Klinefelter Syndromes E Ars Et Alcontrasting
confidence: 50%
“…It seems that meiosis I nondisjunction, in this case, is limited to the XY chromosome pair, probably because this bivalent is the most prone to nondisjunction in male gametogenesis. 19 No correlation was reported between the severity of the Klinefelter phenotype and origin of the extra X chromosome; 20 thus, we cannot predict the KS clinical outcome of this young boy after puberty. However, the early diagnosis of KS in this patient can be considered exceptional since most KS males are not identified until adulthood and it will be extremely helpful in order to anticipate testosterone replacement therapy if necessary.…”
Section: Concurrence Of Alport and Klinefelter Syndromes E Ars Et Almentioning
confidence: 86%
“…Levels of aneuploid sperm in fertile men have been reported to be around 3%-5%; virtually all studies investigating sperm aneuploidy levels in infertile men have demonstrated a significant increase in aneuploidy levels compared to their fertile counterparts. 5,28,29 The vast majority of studies report around a threefold increase in sperm aneuploidy levels in infertile men. Increases in sperm aneuploidy have been reported for all infertility phenotypes including oligozoospermia (low concentration), asthenozoospermia (poor motility) and teratozoospermia (poor morphology).…”
Section: Chromosomal Aneuploidymentioning
confidence: 99%
“…It is clear that increased frequencies are strongly correlated with increasing severity of infertility with the highest levels reported in men with severe oligoasthenoteratozoospermia and sperm retrieved from testicular sperm extraction in cases of non-obstructive azoospermia. 5,28,29 However, despite the increase in aneuploidy frequencies, physicians rarely order aneuploidy screening for a male indication 30 except, perhaps, for a rare case requested based on very low sperm counts and the need for surgical or non-surgical collection of sperm from the testes. This is most likely due to the fact that the issue of increased sperm aneuploidy in certain patient cohorts is a complex one and raises many questions, which remain to be answered.…”
Section: Chromosomal Aneuploidymentioning
confidence: 99%
“…Increased sperm aneuploidy levels have been reported in infertile men for all abnormal semen profiles (oligozoospermia, asthenozoospermia, teratozoospermia and azoospermia). 63,64 This finding has obvious clinical ramifications given the fact that aneuploidy, albeit predominantly maternal in origin (except for the sex chromosomes), is the leading cause of pregnancy loss and developmental disabilities in humans. 47 Increased aneuploidy frequencies in infertile men have been reported for all investigated chromosomes.…”
Section: The Relationship Between Chromosome Aneuploidy and Male Infementioning
confidence: 99%